(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2023)
This article investigates the presence of Phraseological Cultural Markers in the work Capitães da Areia (2008, [1937]) by the Bahian writer Jorge Amado. It is inserted in the field of cultural and phraseological studies from a Portuguese- Spanish contrastive translatological perspective. First, the phraseological cultural markers in the work written in Portuguese in 2008 were catalogued and the Spanish translation was observed in the work translated in 2009. Next, the functioning of phraseological cultural markers has been investigated and these markers have been classified into cultural domains. Finally, the translation modalities used in the Spanish translation were identified. The methodology was developed based on the contributions of Corpus Linguistics and the result of this research is the elaboration of an online bilingual glossary (Portuguese-Spanish).